Soil management instruments for social housing: case analysis (2014)
Land availability is an essential prerequisite for providing housing solutions; however, access to this soil faces administrative, regulatory and technical obstacles that cause chaotic urbanization processes in the main cities of the country. This article discusses management tools for soil availability in current legislation and used in projects developed by Metrovivienda in Bogotá D.C. As a result, we found that the main issues are: scarcity and high land prices and the persistent phenomenon of illegal urbanization aim to meet the unsatisfied demand, especially for people in informal labor market. Currently Public Housing Policy focuses primarily on subsidies to demand allocation and implementation of housing construction projects, but it is necessary the articulation of this Policy with a Public Land Policy that regulates use and land market. Otherwise, a long-term planning and will be very difficult to reduce the gap between supply and demand for housing and achieve an efficient, equitable and orderly development for the city.